Benzalkonium Chloride Adaptation Increases Expression of the Agr System, Biofilm Formation, and Virulence in Listeria monocytogenes - Jiang, Xiaobing; Jiang, Congyi; Yu, Tao; Jiang, Xiaojie; Ren, Siyu; Kang, Rui; Qiu, Shuxing (Frontiers in Microbiology, 2022)
Benzalkonium chloride (BC) is widely used for disinfection in food industry. However, prolonged exposure to BC may lead to the emergence of BC adapted strains of Listeria monocytogenes, an important foodborne pathogen. Until now, two communication systems, the LuxS/AI-2 system and the Agr system, have been identified in L. monocytogenes. This study aimed to investigate the role of communication systems in BC adaptation and the effect of BC adaptation on two communication systems and the communication-controlled behaviors in L. monocytogenes. Results demonstrated that the Agr system rather than the LuxS system plays an important role in BC adaptation of L. monocytogenes. Neither luxS expression nor AI-2 production was affected by BC adaptation. On the other hand, the expression of the agr operon and the activity of the agr promoter were significantly increased after BC adaptation. BC adaptation enhanced biofilm formation of L. monocytogenes. However, swarming motility was reduced by BC adaptation. Data from qRT-PCR showed that flagella-mediated motility-related genes (flaA, motA, and motB) were downregulated in BC adapted strains. BC adaptation increased the ability of L. monocytogenes to adhere to and invade Caco-2 cells but did not affect the hemolytic activity. Compared with the wild-type strains, the expression levels of virulence genes prfA, plcA, mpl, actA, and plcB increased more than 2-fold in BC adapted strains; however, lower than 2-fold changes in the expression of hemolysis-associated gene hly were observed. Our study suggests that BC adaptation could increase the expression of the Agr system and enhance biofilm formation, invasion, and virulence of L. monocytogenes, which brings about threats to food safety and public health. Therefore, effective measures should be taken to avoid the emergence of BC adapted strains of L. monocytogenes.